2018
DOI: 10.1016/j.fct.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Achillea millefolium L. hydroethanolic extract inhibits growth of human tumor cell lines by interfering with cell cycle and inducing apoptosis

Abstract: The cell growth inhibitory activity of the hydroethanolic extract of Achillea millefolium was studied in human tumor cell lines (NCI-H460 and HCT-15) and its mechanism of action was investigated. The GI concentration was determined with the sulforhodamine B assay and cell cycle and apoptosis were analyzed by flow cytometry following incubation with PI or Annexin V FITC/PI, respectively. The expression levels of proteins involved in cell cycle and apoptosis were analyzed by Western blot. The extracts were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…Furthermore, the cell cycle perturbation results of the present work were similar to those observed in a previous study conducted on wild-type p53 H460 cells (but not mutant p53 H460 cells) after the treatment with Achillea millefolium hydroalcoholic extract [39]. Pereira et al (2018) demonstrated the induction of apoptosis and S-phase arrest, with an increased level of p53 and p21 indicating the different mechanisms involved in the Achillea millefolium extract-induced growth arrest. Likewise, a previous study reported that casticin, a flavonoid extracted from Achillea millefolium, caused G 2 /M arrest in HCT116 colon cancer cells, which was confirmed by the induction of p21 and down-regulation of CDK1 [14].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the cell cycle perturbation results of the present work were similar to those observed in a previous study conducted on wild-type p53 H460 cells (but not mutant p53 H460 cells) after the treatment with Achillea millefolium hydroalcoholic extract [39]. Pereira et al (2018) demonstrated the induction of apoptosis and S-phase arrest, with an increased level of p53 and p21 indicating the different mechanisms involved in the Achillea millefolium extract-induced growth arrest. Likewise, a previous study reported that casticin, a flavonoid extracted from Achillea millefolium, caused G 2 /M arrest in HCT116 colon cancer cells, which was confirmed by the induction of p21 and down-regulation of CDK1 [14].…”
Section: Discussionsupporting
confidence: 89%
“…Given this problematic issue, the screening of natural compounds as potential anti-tumor agents has become an interesting approach worldwide. [7][8][9][10][11][12] Most notably, nearly half of the small molecules approved for cancer treatment were either actually natural products or derived from such products. 13 Some of the most relevant anticancer drugs in this category include frequently used agents such as Taxol, vinblastine and camptothecin.…”
Section: Introductionmentioning
confidence: 99%
“…But, reducing the doses of the chemical agent or employing natural compounds can overcome this significant barrier that exists to eliminate CC [11]. Natural or bioactive compounds are used against multiple illnesses including rheumatic, anthelmintic, diuretic, hypoglycaemia and cancer [23].…”
Section: Current Therapies Against Cervical Cancermentioning
confidence: 99%